Utilising the scientific method to demonstrate that slender beam/column behaviour is the dominant behavioural mechanism leading to roof/rib failure - Colwell, Mark; Frith, Russell (International journal of mining science and technology, 2021)
As per most other earth science engineering problems, the underground coal geotechnical environment and the way in which roof and rib support interacts with the rock mass are complex issues. It is therefore generally recognised that without prudent simplification, the complexity of the problem will overwhelm all current geotechnical methods of modelling, not least for the reason that a rock mass can never be characterised to a level that allows a “non-simplified” analysis. The fact that numerical models, which are commonly purported to be a “simulation” tool and the so-called epitome of advanced geotechnical engineering, always need to be “calibrated” to a known reality is taken to be conclusive proof of this statement. While the problem should not be oversimplified (i.e. the dominant failure mechanisms or critical data input parameters should not be ignored), without question judicious simplification is at the heart of all engineering design, to the point that it has a well-established name – “reductionism”. The hypothesis addressed in this paper, is that horizontal and vertical stress-driven slender beam and column behaviour (which includes unstable Euler Buckling) are respectively the dominant (but not only) roadway roof and ribline behavioural mechanism that (if not controlled) can lead to excessive deformation, failure and eventual collapse. As a part of the Scientific Method, a hypothesis can only be tested via real-world observations, measurements and analyses in establishing it is a credible Theory. Utilising the Scientific Method, this paper demonstrates that slender beam/column behaviour is the dominant instability mechanism within a coal mine roof/rib subject to elevated horizontal/vertical stress conditions and therefore, must be representatively accounted for in any credible empirical, analytical, or numerical approach to coal mine roof/rib stability assessment and associated ground support design.